Polymer adhesion, friction, and lubrication - Zeng, Hongbo (Professor in Chemical engineering) (Hoboken, New Jersey : Wiley, 2012)
Specifically dedicated to polymer and biopolymer systems, Polymer Adhesion, Friction, and Lubrication guides readers to the scratch, wear, and lubrication properties of polymers and the engineering applications, from biomedical research to automotive engineering. Author Hongbo Zeng details different experimental and theoretical methods used to probe static and dynamic properties of polymer materials and biomacromolecular systems. Topics include the use of atomic force microscopy (AFM) to analyze nanotribology, polymer thin films and brushes, nanoparticles, rubber and tire technology, sy.
3.5.5 Controlling Wear in Hard Biological Materials: Self-Sharpening Mechanism in Rodent Teeth3.6 Biomimetic and Engineering Approaches of Biolubrication; 3.6.1 Hydrogel Coatings as Artificial Cartilage Materials; 3.6.2 Mimicking Synovial Fluid Lubricating Properties: Polyelectrolytes Lubrication; 3.6.3 Superlubrication by Aggrecan Mimics: End-Grafted Polymers and the Brush Paradigm; 3.6.4 Perspectives and Future Research Avenues; Acknowledgment; References; 4: Polymer Brushes and Surface Forces; 4.1 Introduction; 4.2 Some Generic Properties of Polymer Brushes.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Tribology; Adhesion; Friction; Lubrication and lubricants; Adhesion; Friction; Lubrication and lubricants; Tribology; TECHNOLOGY & ENGINEERING -- Material Science; Adhesion; Friction; Lubrication and lubricants; Tribology; Electronic books; Electronic books